(untitled) (AmeriQuests, 2020)
In light of the backlash from the international community about United States’ practice of family separation of the border, I look at the other countries with similar practices, notably Israel, India, Belize, Canada, the UK, and Norway. Although varying in scale and scope, each of these practices nonetheless has the potential to traumatize a child, damaging their future cognitize maturation. In addition to mental health concerns, the existence of alternatives to detention that have been successfully practiced in countries such as Belgium or Costa Rica give little reason to continue the practice of detaining families. Cover image: Loren Elliott